ANALISIS DAYA TARIK WISATA ALAM HUTAN PELANGI GUNUNG CUPU PURWAKARTA - Kartika, Dewi Gita; Farida, Farida; Jaiman, Tries Handriman (JURNAL KEPARIWISATAAN, 2024)
Purwakarta has 62 tourist destinations in 2023, one of the interesting places to visit is Pelangi Forest, Mount Cupu, Purwakarta. This destination has been established since 2017 on an area of 5 (five) hectares and is still being developed. It is called Pelangi Forest which means Rainbow Forest because it has a unique theme, decorating the forest with lots of colorful ornaments like a Pelangi. However, the level of tourist visits is still very low, it is known that there were only 2,582 tourists per year in 2020. This research aims to analyze the extent of the natural tourism potential of Pelangi Forest. The method used is quantitative descriptive, where data collection is carried out through distributing questionnaires to 30 tourists. The collected data was then analyzed using the Analysis of Operation Area-Natural Tourism Objects and Attractions (Analisis Daerah Operasi Objek dan Daya Tarik Wisata Alam (ADO-ODTWA)) criteria assessment by the Directorate General of PHKA by providing an assessment of each specified indicator. The results obtained were that the Pelangi Forest was suitable for development as a natural tourism objects and attractions (73.92%>66.67%). It is hoped that this research can become a reference and alternative strategy for managing the Pelangi Forest in developing its tourist attraction to be more optimal so that it can increase the number of tourists in the future, as well as being a source of information for other parties who need it through published journals